Frequent Reassortments May Explain the Genetic Heterogeneity of Rotaviruses: Analysis of Finnish Rotavirus Strains - Maunula, Leena (American Society for Microbiology, 2002)
The predominant rotavirus electropherotypes (e-types) during 17 epidemic seasons (1980 through 1997) in Finland were established, and representative virus isolates were studied by nucleotide sequencing and phylogenetic analysis. The virus isolates were either P[8]G1 or P[8]G4 types. The G1 and G4 strains formed one G1 lineage (VP7-G1-1) and one G4 lineage, respectively. Otherwise, they belonged to two P[8] lineages (VP4-P[8]-1 and -2) unrelated to their G types. Phylogenetic analysis of partial sequences of all 11 RNA segments obtained from the strains also revealed genetic diversity among gene segments other than those defining P and G types. With the exception of segments 1, 3, and 10, the sequences of the other segments could be assigned to 2 to 4 different genetic clusters. The results of this study suggest that, in addition to the RNA segments encoding VP4 and VP7, the other RNA segments may segregate independently as well. In total, the 9 predominant e-types represented 7 different RNA segment combinations when the phylogenetic clusters of their 11 genes were determined. The extensive genetic diversity and number of e-types among rotaviruses are best explained by frequent genetic reassortment.